Med Maria valt det bästa: Kring ett nyfunnet Romanbrev - Bengtsson, Britta; Helenius-Öberg, Eva (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 1991)
In the autumn of 1988, Britta and Ingemar Bengtsson found a previously unnoticed source for information concerning Johan Helmich Roman’s (1694-1758) religious songs: a letter, dated in the town of Kalmar on Jan 10th, 1757. It is addressed to Anders Nicander (1707- 1781), a warehouse inspector in the town of Västervik. Nicander is best known as a poet and translator of, among other, latin poetry. The letter deals with Nicander’s authorship and Roman’s own composing. First, there is a commentary on Nicander’s choice of texts for his translations. Nicander could have dealt with classical texts, such as Virgil’s Georgica or Homer’s Iliad , but he chose to work on David’s Psalms. In Roman’s words, Nicander thereby, like Mary, and as opposed to Martha, ”hath chosen that good part” (St. Luke, 10:42). Thereafter, Roman thanks Nicander for the texts based on the Psalms he has sent him and looks forward to receiving further texts, as previously promised. He encloses a composition of his own as well. This newly found letter precises thus the time of creation of a series of compositions by Roman, based on fourteen paraphrases on the Psalms by Nicander. Nicander ought to have finished his work on ”King David’s Psalms in swedish heroic verse” by the mid 1750’s, while Roman had just commenced his work when the letter was written.. Roman, therefore, ought to have composed these songs from the end of 1756 until possibly the beginning of 1758. There is a lot that suggests that the Psalms were, in effect, Roman’s evensong, and that Nicander’s paraphrases were a source of inspiration for the last pieces of music he composed.